Desenvolvimento de pães de fermentação natural cultivado em meio adicionado de açaí em pó - Nogueira, Adriana Machado (2021)
Artisanal techniques for the production of bread are adopted in aim to modify the structure of the bread dough, which can result in products with greater added value. To understand how these changes occur, the application of natural fermentation with modification by the addition of powdered açaí (10%) was adopted. Following type I protocols, two sourdoughs were developed: FNT and FNA, applied in four formulations with short (first 120 days) and long (after one year) fermentation, and evaluated by physical, physicochemical and microscopic analyses. Natural fermentation with modification of the culture medium by the addition of powdered açaí (FNA) has characteristics similar to those of sourdough exclusively from wheat (FNT), with a delay of a few days for its stabilization and slightly higher pH. In addition, no variations were found in centesimal composition or microscopic characteristics significantly different between samples, with the exception of color. The newly produced sourdough is able of producing breads with a more acidic pH, despite the tendency to reach values ​​close to those of traditional doughs over time. Long fermentation improves the averages of parameters in the fermentation test and instrumental texture compared to short fermentation breads. Concluding that the adaptation of the microorganism to the substrate improves the final texture of the product. With the simple addition of açaí powder there is an increase in hardness, but when added to sourdough it caused a slight reduction in texture parameters. Regardless of the fermentation time, the addition of açaí to the bread dough slightly contributes to decreasing the expansion index and increasing the number of alveoli without modifying their circularity, it is also the main responsible for changing the color of the samples, specifically in the crumb. Acidification, high number of alveoli in breads with non-gluten-forming flours, increased fiber content and especially the reorganization of the microscopic structure of the crumb, indicate the formation of resistant starch, in addition, the long fermentation shows more starch granules firmly adhered to the dough. In summary, the results obtained in natural fermentation breads are similar to the control formulation. In the same way that breads with açaí in the formulation had superior characteristics than expected, proving the application of the natural fermentation technique in baking to obtain breads with desirable characteristics, that is, with the modification of sourdough it is possible to improve weaker doughs, and provide products with superior quality.